2006
DOI: 10.1111/j.1444-2906.2006.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, stress tolerance and non-specific immune response of Japanese flounder Paralichthys olivaceus to probiotics in a closed recirculating system

Abstract: Effects of probiotics on growth, stress tolerance and non-specific immune response in Japanese flounder Paralichthys olivaceus were evaluated in a closed recirculating system. Survival and growth of flounder treated by supplying commercial probiotics either in the diet (the probiotic diet group), or into the rearing water (the water supply group), were higher compared to the untreated group (the control group). Water quality parameters, pH, NH 4 -N, NO 2 -N and PO 4 -P showed lower concentration in the probiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(143 citation statements)
references
References 40 publications
10
127
1
5
Order By: Relevance
“…They could improve growth performance and feed conversion efficiency of fish by producing short chain fatty acids, digestive enzymes and vitamins (Martínez et al, 2012), enhance immune response by effecting T-cell differentiation ( Merrifield et al, 2010), provide resistance to pathogenic organisms ( Muñoz-Atienza et al, 2013) and increase tolerance under stressful condition (Varela et al, 2010). Moreover, also assure the digestion of anti-nutritional factors (Suzer et al, 2008), enhance fish appetite, improve carcass and flesh quality (van Nuenen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They could improve growth performance and feed conversion efficiency of fish by producing short chain fatty acids, digestive enzymes and vitamins (Martínez et al, 2012), enhance immune response by effecting T-cell differentiation ( Merrifield et al, 2010), provide resistance to pathogenic organisms ( Muñoz-Atienza et al, 2013) and increase tolerance under stressful condition (Varela et al, 2010). Moreover, also assure the digestion of anti-nutritional factors (Suzer et al, 2008), enhance fish appetite, improve carcass and flesh quality (van Nuenen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies utilize stress challenges to replay information of an organisms fitness or quality (Dhert et al, 1992;Taoka et al, 2006;Salze et al, 2008). Indeed, salinity stress challenge has been frequently used for determination of fry quality in nutritional studies (Smith et al, 2004;Taoka et al, 2006;Salze et al, 2008) and this the reason for developing this assay in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, salinity stress challenge has been frequently used for determination of fry quality in nutritional studies (Smith et al, 2004;Taoka et al, 2006;Salze et al, 2008) and this the reason for developing this assay in the present study. Our results demonstrate that Primalac had no effect on survival of the Caspian roach.…”
Section: Discussionmentioning
confidence: 99%
“…Kim & Austin (2006) recorded high gut mucosal lysozyme activity in fish fed with Caronbacterium divergens B 33 and Carnobacterium maltaromaticum B26. Taoka et al, 2006, also reported an enhanced lysozyme level in tilapia fed with live and dead probiotics and recorded a high survival rate when challenged with Edwardsiella tarda. Panigrahi et al, 2004, showed significantly higher lysozyme activity in rainbow trout fed with Lactobacilllus rhamnosus.…”
Section: Lysozyme Activitymentioning
confidence: 99%
“…Taoka et al, 2006 indicated that probiotics supplied in the rearing water and the diet of fish enhanced the stress tolerance and the non-specific immune system of Japanese flounder, providing them a higher resistance against stress conditions and pathogens. It has been demonstrated that oral administration of Clostridium butyricum bacteria to rainbow trout enhanced the resistance of fish to vibriosis, by increasing the phagocytic activity of leucocytes (Sakai et al, 1995).…”
Section: Immunological Assaysmentioning
confidence: 99%